Produtos naturais como candidatos a fármacos úteis no tratamento do mal de Alzheimer - Viegas Jr., Cláudio [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Furlan, Maysa [UNESP]; Manssour Fraga, Carlos Alberto; Barreiro, Eliezer J. (FapUNIFESP (SciELO), 2004)
Alzheimer's disease (AD) is a progressive neurodegenerative pathology with severe economic and social impact. There is currently no cure, although cholinesterase inhibitors provide effective temporary relief of symptoms in some patients. Nowadays drug research and development are based on the cholinergic hypothesis that supports the cognition improvement by regulation of the synthesis and release of acetylcholine in the brain. There are only four commercial medicines approved for treatment of AD and natural products have played an important role in the research for new acetylcholinesterase inhibitors.
Natural products as candidates for useful drugs in the treatment of Alzheimer's disease
Keywords: Acetylcholinesterase; Alzheimer's disease; Natural products; 11 hydroxygalantamine; 9 o norgalantamine; acetylcholine; cholinesterase inhibitor; donepezil; galantamine; Ginkgo biloba extract; natural product; rivastigmine; tacrine; unclassified drug; acetylcholine release; Alzheimer disease; brain function; cholinergic activity; cognition; conference paper; degenerative disease; drug efficacy; drug indication; drug synthesis; economic aspect; hypothesis; neuropathology; regulatory mechanism; social aspect